Lecturers' enthusiasm, lecturer student rapport and student satisfaction at selected Malaysian polytechnics - Salomawati binti Ishak (Institute of Education, International Islamic University Malaysia., 2011)
The aim of this study is to examine the influence of lecturers' human capital i.e. lecturers enthusiasm and rapport towards student satisfaction i.e. teaching- learning and mentoring services at selected Malaysian Polytechnics. Theoretical framework was derived from human capital theory, resource based view and students satisfaction theory. The model of this study was originated from performance model. The respondents comprised of 200 polytechnics students from the five clustered regions all over the country. Data were collected using structured 26 items adapted questionnaires using clustered systematic sampling method. The independent variables were the lecturers' enthusiasm and rapport while the dependent variables were teaching and mentoring. The dimensions of enthusiasms, rapport, teaching and mentoring were determined using Principal Component Analysis (PCA) and Confirmatory Factor Analysis (CFA) techniques. A full fledged Structural Equation Modeling (SEM) analysis using AMOS 4 data fitting program was conducted to determine the inter-relationships among the variables. The analysis found that enthusiasm and rapport were significantly related to teaching-learning and mentoring services. But rapport was indirectly and significantly related to teaching-learning through enthusiasm. Apart from that mentoring was directly and significantly related to teaching-learning. This study provides an insight and further understanding of the impact of enthusiasm and rapport on polytechnic performances in terms of student satisfaction. It also stresses on the importance of lecturer-student relationship in rendering quality educational services. Keywords: lecturers' human capital, lecturers' enthusiasm, students-lecturers rapport student satisfaction, organizational performance